A modular approach to enzymatic ligation of peptides and proteins with oligonucleotides - Tan, Derrick Jing Yang (2022)
Joining peptides and oligonucleotides offers potential benefits, but current methods remain laborious. Here we present a novel approach towards enzymatic ligation of the two modalities through the development of tag phosphoramidites that readily couple onto oligonucleotides. This simple and highly efficient approach paves the way towards streamlined development and production of peptide/protein-oligonucleotide conjugates.